Parvovirus B19 DNA detectable in hearts of patients with dilated cardiomyopathy, but absent or inactive in blood. (1st May 2021) - Russcher, Anne; Verdonschot, Job; Molenaar‐de Backer, Marijke W.A.; Heymans, Stephane R.B.; Kroes, Aloys C.M.; Zaaijer, Hans L.
Abstract: Aims: Parvovirus B19 (B19V) is often assumed to be a cause of dilated cardiomyopathy (DCM), based on the quantification of B19V DNA in endomyocardial biopsies (EMB). Whether the presence of B19V DNA correlates with active infection is still debated. Application of the enzyme endonuclease to blood samples results in degradation of B19V DNA remnants but leaves viral particles intact, which enables differentiation between active and past infection. In this study, the susceptibility to degradation by endonuclease of B19V DNA in blood was compared between DCM patients and a control group of recent B19V infections. Methods and results: Twenty blood samples from 20 adult patients with DCM, who previously tested positive for B19V DNA in EMB and/or blood, were tested with B19V PCR before and after application of endonuclease to the samples. Six blood samples tested positive for B19V DNA with a mean viral load of 2.3 × 10 4  IU/mL. In five samples, B19V DNA became undetectable after endonuclease (100% load reduction); in one sample DNA load showed a 23% log load reduction (viral load before endonuclease: 9.1 × 10 4  IU/mL; after: 6.5 × 10 3  IU/mL). Presence of cardiac inflammation did not differ between patients with B19V DNAemia (1/4) and patients without B19V DNAemia (6/14) ( P value = 1.0). In all 18 control samples of proven recent B19V infections, DNA remained detectable after application of endonuclease, showing only a mean log load reduction of 2.3% (mean viral load before endonuclease: 8.1 × 10 11  IU/mL; after: 8.0 × 10 11  IU/mL). Load reduction differed significantly between the DCM group and the control group; indicating the presence of intact viral particles in the control group with proven active infection and the presence of DNA remnants in the DCM group ( P value = 0.000). Conclusion: During recent B19V infection, viral DNA levels in blood were unaffected by endonuclease. In contrast, B19V DNA in blood in patients with DCM became undetectable or strongly reduced after application of endonuclease. Circulating viral DNA in this subset of patients with presumed parvovirus‐associated DCM does not consist of intact viral particles. Viral replicative activity cannot be assumed from demonstrating B19V DNA in cardiac tissue or in blood in DCM patients.